2006
DOI: 10.1111/j.1574-6941.1997.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

A unifying hypothesis for the structure of microbial biofilms based on cellular automaton models

Abstract: A review of the basic structure of microbial biofilm reveals that at least three conceptual models exist: (i) heterogeneous mosaic biofilm, (ii) penetrated water‐channel biofilm and (iii) dense confluent biofilm. When consideration is given to the effects of growth resource, it may be that all three variants are correct but form at widely different substrate concentrations. Experimental research with bacterial colonies and models of the latter using cellular automata have confirmed this view. Use of cellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(53 citation statements)
references
References 27 publications
1
50
0
2
Order By: Relevance
“…Mathematical models that capture spatial structure and stochastic effects down to the level of individuals have now been applied widely to various biological systems (Durrett & Levin, 1994a, b;Hanski & Gilpin, 1997;Tilman & Kareiva, 1997;Durrett & Levin, 1998;Dieckmann et al, 2000), including some that involve microbial communities (Durrett & Levin, 1997;Wimpenny & Colasanti, 1997;Kreft et al, 1998;Picioreanu et al, 1998aPicioreanu et al, , b, 2004Kerr et al, 2002;Kreft & Bonhoeffer, 2005;Wei & Krone, 2005;Xavier et al, 2005;Krone & Guan, 2006;Mochizuki et al, 2006). These individual-based lattice models are of several types.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models that capture spatial structure and stochastic effects down to the level of individuals have now been applied widely to various biological systems (Durrett & Levin, 1994a, b;Hanski & Gilpin, 1997;Tilman & Kareiva, 1997;Durrett & Levin, 1998;Dieckmann et al, 2000), including some that involve microbial communities (Durrett & Levin, 1997;Wimpenny & Colasanti, 1997;Kreft et al, 1998;Picioreanu et al, 1998aPicioreanu et al, , b, 2004Kerr et al, 2002;Kreft & Bonhoeffer, 2005;Wei & Krone, 2005;Xavier et al, 2005;Krone & Guan, 2006;Mochizuki et al, 2006). These individual-based lattice models are of several types.…”
Section: Introductionmentioning
confidence: 99%
“…3). Bacteria form a thick biofilm under rich nutrient conditions and a very thin biofilm under poor nutrient conditions (Wimpenny et al, 1997). For this reason, lack of nutrients can prevent P. putida from forming biofilm.…”
mentioning
confidence: 99%
“…For process optimization, the spatial distribution of the different types of microorganisms, and therefore the reactions in the biofilm, may be controlled by varying the operational conditions such as surface loading rate, upflow fluid velocity, and oxygen supply. Other studies also demonstrated the possible structural change of the biofilms as a result of the differences in the local substrate availability (33)(34)(35), or upflow fluid velocity outside the biofilm in the reactor (20). Future studies will be directed to further examine the influence of the operation parameters on the biofilm structures and functions for more effective treatment of organonitrile wastewater by the MABR technology.…”
Section: Resultsmentioning
confidence: 96%